SEJARAH UMUM KONFLIK JUGUN IANFU DI KOREA SELATAN - Lumbantobing, Sarah Sonia Theresia; Jamaan, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The purpose of this research is to know how the general description Jugun Ianfu. This article will also explain the history of Japanese colonialism in Southeast Asia, which countries were invaded by Japan after the Meiji Restoration. In Japan during it’s occupation there were issues that ended in historical conflicts, namely regarding sexual licenses or known as Jugun Ianfu. It will also be explained why there jugun ianfu during Japanese invasion and how this conflict arose as a conflict between the various countries it had colonized. This research is analyzed using qualitative methods with library data collection techniques or known as library research. Using the theory of international cooperation by K. J Holsti, said that the existence of a collaboration is formed from the existence of interests to be achieved through a meeting, promoted. In this theory the aim of each country is for bilateral realtions which had been tenuous due to the problem of comfort women to get a solution. The Agreement on Comfort Women is a way to achieve god bilateral relations. The result in this research is the reason for the existence of jugun ianfu in the Japanese Colonial era because the Japanese Government at that time minimized the spread of venereal disease for its soldiers and as an entertainer and statisfaction of their sexual desires. Keywords: Jugun ianfu, South Korea, Sexual Slavery, World War II.